Phytoplasma Infection Influences Gene Expression in American Cranberry - Pradit, Nakorn; Rodriguez-Saona, Cesar; Kawash, Joseph; Polashock, James (Frontiers in Ecology and Evolution, 2019)
Cranberry false blossom disease (CFBD) is caused by a leafhopper-vectored phytoplasma infection. CFBD results in distinctive branching of the upright shoots (witches’ broom) and the formation of deformed flowers that fail to produce fruit. This disease is reemerging and poses a serious threat to the cranberry industry. To determine the impact of the disease on host gene expression, we compared the transcriptome profiles between plants with CFBD and uninfected cranberry plants. We found that phytoplasma infection induced the expression of 132 genes, while suppressing 225 genes, compared to uninfected cranberry plants. Differentially expressed genes between uninfected and infected plants were largely associated with primary and secondary metabolic, defensive, and developmental pathways. Phytoplasma infection increased the expression of genes associated with nutrient metabolism, while suppressing genes associated with defensive pathways. This expression profile change supports the “host manipulation hypothesis,” whereby CFBD enhances host quality for insect vectors, thus promoting phytoplasma transmission.